Isolation, characterization, and genome insights into an anaerobic sulfidogenic Tissierella bacterium from Cu-bearing coins. (April 2019) - Bukhtiyarova, Polina A.; Antsiferov, Dmitry V.; Brasseur, Gael; Avakyan, Marat R.; Frank, Yulia A.; Ikkert, Olga P.; Pimenov, Nikolay V.; Tuovinen, Olli H.; Karnachuk, Olga V.
Abstract: Recent reports on antimicrobial effects of metallic Cu prompted this study of anaerobic microbial communities on copper surfaces. Widely circulating copper-containing coinage was used as a potential source for microorganisms that had had human contact and were tolerant to copper. This study reports on the isolation, characterization, and genome of an anaerobic sulfidogenic Tissierella sp. P1from copper-containing brass coinage. Dissimilatory (bi)sulfite reductase dsrAB present in strain P1 genome and the visible absorbance around 630 nm in the cells suggested the presence of a desulfoviridin-type protein. However, the sulfate reduction rate measurements with 35 SO4 2− did not confirm the dissimilatory sulfate reduction by the strain. The P1 genome lacks APS reductase, sulfate adenylyltransferase, DsrC, and DsrMK necessary for dissimilatory sulfate reduction. The isolate produced up to 0.79 mM H2 S during growth, possibly due to cysteine synthase (CysK) and/or cysteine desulfhydrase (CdsH) activities, encoded in the genome. The strain can tolerate up to 2.4 mM Cu 2+ (150 mg/l) in liquid medium, shows affinity to metallic copper, and can survive on copper-containing coins up to three days under ambient air and dry conditions. The genome sequence of strain P1 contained cutC, encoding a copper resistance protein, which distinguishes it from all other Tissierella strains with published genomes. Graphical abstract: Image 1 Highlights: An anaerobic sulfidogenic Tissierella sp. strain P1 survives on Cu-bearing coins. Despite the dsrAB occurrence strain P1 could not dissimilate sulfate. H2 S can be produced by cysteine synthase and/or cysteine desulfhydrase encoded in the strain P1 genome. O2 reduction by the bd menaquinol oxidase and iron sulfide formation by P1 cells may play a role in oxygen tolerance. Strain P1 has affinity to Cu 0 .